Treatment outcomes after articular eminectomy in patients with long-standing/habitual temporomandibular joint dislocation. Issue 3 (May 2018) - Ohta, Ryousuke; Yamada, Shin-ichi; Naruse, Tomofumi; Yoshimura, Hitoshi; Sakurai, Akinari; Ishii, Shutaro; Tomioka, Takahiro; Sano, Kazuo; Umeda, Masahiro; Shibahara, Takahiko; Kurita, Hiroshi
Abstract: The frequency of temporomandibular joint dislocation is higher in elderly patients and especially those with psychiatric or cerebral disease. The purpose of this study was to investigate the efficacy of articular eminectomy for long-standing/habitual dislocation of the temporomandibular joint in elderly patients based on a retrospective analysis at 3 institutes. Sixteen patients with long-standing/habitual temporomandibular joint dislocation were treated with articular eminectomy in accordance with Myrhaug's method, i.e., the condyles were repositioned to prevent re-dislocation. Although 1 patient required 2 operations, all patients were treated successfully without major complications and the treatment success rate was 93.8%. Articular eminectomy increased the ease of reduction with open repositioning of the condyle into the glenoid fossa and was effective for preventing future dislocation of the temporomandibular joint in especially elderly patients.